Desenvolvimento de carregador embarcado para veículos elétricos baseado em conversor estático com isolação capacitiva - Toebe, Ademir (2025)
This Thesis presents academic and technological contributions achieved in the field of power electronics. The work addresses capacitive isolation as a means of energy transfer while simultaneously acting to limit touch current, thereby enhancing safety in applications such as vehicle chargers. Initially, relevant standards that establish safety criteria and practices are analyzed, aiming to develop a proposal aligned with practical applicability. Subsequently, the literature review identified various solutions and applications of capacitive isolation, including in non-conductive energy transfer systems for electric vehicle charging. Several topologies employing capacitive isolation were studied, evaluating their advantages and disadvantages. This led to the formulation of a topology compatible with the buck converter, but offering a higher degree of safety. Theoretical analyses and simulations demonstrated the feasibility of the proposed approach, and a pilot prototype was built and assessed in terms of energy processing and touch current limitation. Comparative evaluations with the LLC converter topology highlighted advantages of the proposed solution regarding volume, number of semiconductor devices, and efficiency. Next, a detailed analysis was conducted on the impact of rectifiers on touch current, demonstrating the benefits of using symmetric DC bus rectifiers, which, combined with the proposed topology, further enhance system safety. Finally, an on-board charger (OBC) for electric vehicles was designed and implemented. This OBC comprises two Vienna rectifiers connected in parallel and interleaved at the input, along with two modules employing the ISOS (Input Series, Output Series) topology used to control battery charging. Experimental results confirmed the effectiveness of the solution, achieving a global peak efficiency of 95%. Additionally, leakage currents through the protective earth conductor, originating from Y-capacitors connected to the battery, were evaluated. Finally, touch current tests performed with a residual current device (RCD) in the circuit demonstrated that the current is reduced to safe levels before the device actuates.